Clinical utility of essential oils in women’s health for phytotherapeutic treatment of candidiasis: a systematic review with emphasis on the potential of copaiba oil (Copaifera sp) from Brazilian biodiversity and technological perspectives applied to biomedicine - Reis, Hugo Diniz; Bezerra, Thallita Rodrigues; Gonçalves, Rosana Fabrício; Lievore, Cecília Conopca; Vidal, Bruna Teixeira; da Silva Filha, Manuela Bandeira; Anjos, Fabiana Cândida de Queiroz Santos; Pegoraro, Fábio; de Bessa, Pedro Faria; de Bessa, Nelita Gonçalves Faria (Seven Editora, 2023)
The clinical application of essential oils has been prospected in recent years from the results of experimental laboratory tests, including the verification of antimicrobial and anti-inflammatory action. Brazil is one of the largest producers of essential oils and has in its mega biodiversity an alternative of institutional, social, environmental and economic development, considering the necessary and current perspective of strengthening the sustainability agenda. In Brazil, vulvovaginal candidiasis is the second most frequent type of vulvovaginitis that affects women’s health, and is caused by the fungus Candida albicans. This is an organism from the resident microbiota of some organs and that, in excess, causes an uncomfortable clinical picture, capable of drastically influencing the patient’s daily life, which makes its effective treatment of utmost importance. As essential oils (EOs) from medicinal plants have shown potential efficacy and reduced side effects, their use as a possible herbal medicine for clinical purposes against candidiasis should be explored. The aim of this study was to elucidate scientific evidence on the use of EOs from plant species, with emphasis on Copaiba oil from Brazilian biodiversity, and its antimicrobial activity against Candida. It is expected to have subsidies regarding safety and efficacy for clinical trials in patients with vaginosis, since there are currently gaps in knowledge about these indicators. In this systematic review study, electronic searches of articles in the CAPES, PubMed, SciELO and LILACS databases were carried out, using as inclusion criteria in vitro (anti-culture) and in vivo studies (clinical and/or pre-clinical trials) that addressed the use of EOs, their phytochemical constituents and comparative Azo Groups as fungistatic drugs, Minimum Inhibitory Concentration (MIC) and Minimum Fungicidal Concentration (MFC) of the EO, Cytotoxicity tests and effects of the EO against fungal infections in animals. EOs were found to be effective as a treatment, especially in strains resistant to the usual drugs, and no adverse reactions, toxicity or changes in formation were identified in vitro tests performed on pregnant and non-pregnant mice. The copaiba oil (Copaifera sp), present in the rich biodiversity of the Brazilian flora, presents satisfactory antimicrobial action against C. albicans and with absence and/or low toxicity in certain conditions, being a relevant indicator for clinical tests. Other essential oils native to Brazil and/or originating from exotic useful plants present phytotherapeutic potentials. It is necessary and urgent to advance in learning and adopting digital technologies, especially in research involving epidemiological and/or clinical data to substantiate the decision-making in terms of public health policies. As perspectives of microbiological assays and clinical tests with essential oils, as in the case of this study, there are still gaps in the development of studies carried out, where the use of digital technology is certainly an increasingly urgent need due to the relevance of agility in research protocols, methodological procedures and analysis of their results. Universities, either through undergraduate or graduate courses, as in areas of knowledge such as biological and health sciences, either medicine, pharmacy or even information technology and engineering, such as biomedical engineering, among others, urgently need to strengthen the area of digital technology and innovation in the teaching-learning process and knowledge practices. The research funding agencies, whether public or private, need to give special attention to the technological era for research, laying a more dynamic foundation for decision-making and the implementation of sectoral public policies. DOI: https://doi.org/10.56238/colleinternhealthscienv1-054